Molecular docking and antiviral activity of N-substituted benzyl/phenyl-2-(3, 4-dimethyl-5, 5-dioxidopyrazolo[4, 3-c][1, 2]benzothiazin-2(4H)-yl)acetamides. Issue 6 (15th March 2015) - Ahmad, Matloob; Aslam, Sana; Rizvi, Syed Umar Farooq; Muddassar, Muhammad; Ashfaq, Usman Ali; Montero, Catherine; Ollinger, Olivia; Detorio, Mervi; Gardiner, John M.; Schinazi, Raymond F.
Graphical abstract